i have to say i'm proud that even i can help out someone:

i got the solution to the 2 task...it actually couldn't be easier.

6/(x-2) - 1/(x+5) = 2/x^2+3x-10

6/(x-2) - 1/(x+5) = 2/(x-2)(x+5) /(x-2)(x+5)

6(x+5) - (x-2) = 2

6x+30-x+2=2

5x = -30 /:5

x = -6

see?? not so hard...the only thing that you HAVE to notice is x^2+3x-10, which can also be written in form of (x-2)(x+5)

when u multiply the first two variables of each bracket (x,x) you get the X^2, when you sum up the second two variables (-2, 5) you get the 3x, and when u multiply them (-2, 5) you get the -10.

that's the way this thing works. you practice that, you have to be experienced enough to spot this as soon as you look at the exercise.

hope i've been helpful